Error Repetition after Direct Written Corrective Feedback in Students’ Writing (RETAIN, 2017)
Error Repetition after Direct Written Corrective Feedback in Students’ Writing Ida Kusuma Parwati English Language Teaching, Language and Art Faculty, State University of Surabaya idaparwati@mhs.unesa.ac.id Ahmad Munir English Language Teaching, Language and Art Faculty, State University of Surabaya ahmadmunir@unesa.ac.id Abstract This study had two purposes; the first purpose was to investigate what the repeated errors made by the students in their subsequent writing after being given direct written corrective feedback by the teacher. The second purpose was to explain why the students repeat errors in their subsequent writing. The study used qualitative research. There were two data of this study. First data were students’ errors in their essay. The students’ errors in their essay consist of students’ errors in the first essay (first draft of first essay that has already given feedback, unrevised version) and students’ errors in their subsequent essay (first draft of next essay that has already given feedback, unrevised version). The second data were students’ oral statements about the reasons why they repeat errors in their subsequent writing. There were two findings of this study. First, there were 11 types of repeated error in students’ writing. Those were noun ending, auxiliary, article, word choice, spelling, preposition, word form, verb form, subject verb agreement, omitted word, unnecessary word. The second finding, there were 4 reasons of repeating errors. Those are analogical error, interlingual transfer, and carelessness of learning. Also, the last reason was there were no explanation about the feedback given and no conference between teacher and student after giving direct written corrective feedback Keywords: Error, Direct Written Corrective Feedback, Repeated Error. Abstrak Penelitian ini memiliki dua tujuan. Tujuan yang pertama adalah untuk menginvestigasi kesalahan apa yang diulang oleh para siswa di tulisan mereka yang selanjutnya setelah diberi direct written corrective feedback oleh guru. Tujuan yang kedua adalah untuk menjelaskan mengapa para siswa mengulang kesalahan di tulisan mereka yang selanjutnya. Penelitian ini menggunakan pendekatan kualitatif. Ada dua data di penelitian ini. Data pertama adalah kesalahan para siswa di tulisan mereka. kesalahan para siswa tersebut terdiri dari kesalahan para siswa di tulisan pertama mereka (draf petama dari tulisan pertama yang sudah diberi direct wrtten corrective feedback, versi yang belum direvisi) dan kesalahan para siswa di tulisan mereka yang selanjutnya (draf pertama dari tulisan yang selanjutnya, yang sudah dibeberi direct written corrective feedback, versi yang belum direvisi). Data yang kedua adalah pernyataan lisan para siswa tentang alasan-alan mengapa mereka mengulang kesalahan di tulisan mereka yang selanjutnya . Ada dua hasil dari penelitian ini. Pertama, ada 11 kesalahan yang dulang oleh siswa di tulisan yang selanjutnya. Yaitu, noun ending, auxiliary, article, word choice, spelling, preposition, word form, verb form, subject verb agreement, omitted word, unnecessary word. Hasil yang kedua adalah ada 4 alasan mengapa mengulang error. Yaitu, analogical error, interlingual transfer, and carelessness of learning. Serta, alasan yang terakhir adalah tidak adanya penjelasan tentang feedback yang diberkan dan tidak ada tanya jawab antara guru dan siswa setelah pemberian direct written corrective feedback. Kata kunci: Kesalahan, Direct Written Corrective Feedback, Kesalahan yang Diulang.